Vacant rooms? The secondary use of stem-galls by ants in Eremanthus erythropappus (Asteraceae) - Santos, Jean Carlos; Maruyama, Pietro Kiyoshi; Fernandes, Geraldo Wilson (Journal of Environmental Analysis and Progress, 2021)
Galls are atypical proliferations of plant tissue induced by highly specialized herbivores, such as some insect groups. Although gall inducers create these structures for their own purpose (food, habitat, protection against natural enemies, and harsh weather), many other organisms can use galls as secondary inhabitants. The creation of new and better habitats with ameliorated micro-environmental conditions allows for the use of many other organisms, and as such, some galling insects are considered "micro" ecosystem engineers. This study characterized the occurrence of ants in microhabitats created by a gall-inducing cecidomyiidae associated with Eremanthus erythropappus (DC.) Mac. Leish (Asteraceae). It was 153 individuals of ants belonging to three species in 19 galls (9.5%) from the 200 galls sampled. The most common ant species found was Myrmelachista gallicola Mayr (Formicinae), including a single queen and larvae individuals. Galls occupied by these ants were 11.5% larger compared to unoccupied galls (gall diameter: occupied galls - 10.00 ± 2.09 mm; unoccupied galls - 8.97 ± 1.90 mm). Abandoned galls might promote the diversity of other organisms, especially for opportunistic dwellers such as ants.